Phenomenology Study of the Socio-Economic Strengthening of the Mentawai Indigenous Peoples - Margaretha Ardhanari; Gratianus Edwi Nugrohadi; Sebastiana Viphindrartin (Trunojoyo University of Madura, 2021)
Regional development, which is an integral part of national development, is aimed more at matters of improving the quality of society, optimal economic growth, expansion of the workforce, and improvement of people's standards of living, for the sake of prosperity. This well-being is understood more holistically, which covers both economic and psychological well-being. One strategy that can be taken is to use the empowerment model. The articulation of this concept in indigenous peoples' context, which is still widely found in Indonesia, assumes a useful model and is ready to be implemented. This study tries to answer these questions. All of which are formulated based on the experience of researcher involvement for two and a half years. It used a qualitative approach to the phenomenological model. Research participants were determined by setting specific criteria (purposive). Data obtained through a process of depth interviews, focus group discussions (FGD), and structured observations which are then processed using inductive thematic analysis after going through a process of communicative and argumentative validation. The results of this study state that the efforts to empower indigenous peoples (specifically the Mentawai people) are realized through a local kinship system (muntoghat), which is also called uma. Because of the large number of muntoghat, the empowerment effort was then followed up using a broader local kinship system called inter-uma. In this uma and inter-uma, the participants are empowered socially, and economically (socio-economic). The process is then followed up with social and juridical institutionalization, and also the development of networks, involving business people, government, academics, and other independent institutions.